Kreativitas Mahasiswa dalam Mengembangkan Paragraf melalui Pembelajaran Bahasa Indonesia dengan Pendekatan PBL (Indonesian Journal of Learning Education and Counseling, 2018)
The purpose of this study was to measure students' creativity in developing paragraphs after learning Indonesian with the PBL approach. The type of research used is quantitative descriptive by comparing the creativity between before and after using the work of students using a rubric of creativity. The results showed an increase in the average student creativity classically by 6.13%. These results indicate that PBL is able to increase student creativity. Application of discussions in small groups on application